Comparative study between conventional hemorrhoidectomy and electrothermal bipolar vessel sealer for Grade IV hemorrhoids - Chaudhary, Devendra; Vijay Kumar Tekam,; Sourabh Mishra,; Singh, Priyanka (Asian Journal of Medical Sciences, 2022)
Background: Hemorrhoids are vascular formations in the anal canal that is also known as piles. They serve as a cushioning of anterior venous channels and connective tissue in its natural condition, which aids in stool management. During defecating, internal hemorrhoids are frequently accompanied by painless, bright crimson rectal discharge. External hemorrhoids can cause discomfort and edema in the anus region. Aims and Objectives: The objectives of this study are to “compare between electrothermal bipolar vessel sealer hemorrhoidectomy versus conventional hemorrhoidectomy in patient of Grade IV hemorrhoids. Materials and Methods: The present study conducted in patients admitted in Gandhi medical college associated Hamidia Hospital, Bhopal carried out in the Department of General Surgery from April 2015 to September 2017. A total of 80 patients were included in the study with comparison between conventional hemorrhoidectomy (n=36) and electrothermal bipolar vessel sealer (ETBVS) (n=44) and comparison of recurrence of complications in them. Results: The mean surgical time was much shorter in ETBVS, as was post-operative pain, which was primarily reduced on the third and 4th post-operative days: discomfort also vanished quicker in ETBVS than in conventional procedure. ETBVS patients had less time off work, a shorter hospital stay, and a reduced risk of total problems. When compared to conventional procedures, the average length of operation in ETBVS was also much shorter (P<0.0001). Conclusion: When a considerable amount of tissue needs to be removed, ETBVS hemorrhoidectomy is a good option. This research confirms its usage as a first-line therapy for Grade IV hemorrhoids.